CONDITIONS AND ORGANIZATION OF THE TRANSITION TO BASIC TECHNOLOGIES OF A NEW TECHNOLOGICAL STRUCTURE - B. L. Bourov; E. S. Dashut; N. I. Komkov (Модернизация, инновация, развитие, 2016)
With due account for the coming new (VI-th) world technological structure, future creation of new types of industrial production is both possible and necessary. Economic environment conditions favorable for such development are designated. In reference to Russian technological environment particulars, self-developing economic-technological microenvironment of a new quality level should be created in zones where controlled «technological chains» function. Possibilities of creation of the VI-th technological structure level basic technologies are shown for industrial and household waste processing techniques as an example.